2017
DOI: 10.1039/c6gc01969b
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective biocatalytic synthesis of monoacylglycerides in sponge-like ionic liquids

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…3,[20][21][22] Its choice relied also on the intermediate nature of the interactions present, when compared with the ILs previously studied via surface freezing, in terms of the van der Waals interactions due to its medium size alkyl chain length, yet with strong coulombic interactions resulting from the [BF 4 ] À anion. This ILC was shown to be an exceptional medium for the selective synthesis of monoacylglycerides 23 and a promising nuclear magnetic resonance (NMR) alignment medium. 24…”
Section: Introductionmentioning
confidence: 99%
“…3,[20][21][22] Its choice relied also on the intermediate nature of the interactions present, when compared with the ILs previously studied via surface freezing, in terms of the van der Waals interactions due to its medium size alkyl chain length, yet with strong coulombic interactions resulting from the [BF 4 ] À anion. This ILC was shown to be an exceptional medium for the selective synthesis of monoacylglycerides 23 and a promising nuclear magnetic resonance (NMR) alignment medium. 24…”
Section: Introductionmentioning
confidence: 99%
“…is an example of a temperature switchable ionic liquid/solid phase used for the selective synthesis of monoglycerides [36]. Monomyristin can also be produced through two stages of reaction of ethyl myristate with 1,2-Oisopropylidene glycerol (mol ratio 1:8) using K 2 CO 3 as a catalyst, which produces an intermediate isopropylidene glycerol myristate as a yellowish liquid with a yield of 32.12% and purity of 95.55%.…”
Section: Monomyristinmentioning
confidence: 99%
“…This problem was mentioned explicitly by some authors (precaution was taken to suppress its effect) [ 12 ] but not others [ 13 ], even when the ILBSs were heated with methanol at 85 ° C for 8 h [ 14 ]. A literature survey using the search terms (HF, pH and hydrolysis) for the above-mentioned ILBSs showed that the time elapsed between preparing the ILBS solutions and the measurements/applications was not mentioned [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Therefore, we stress that this instability problem should not be overlooked; its potential effect on micellar parameters and other applications should be assessed.…”
Section: Introductionmentioning
confidence: 99%